PERLINDUNGAN KONSUMEN ATAS PEREDARAN OBAT SIRUP DI INDONESIA (STUDI KASUS OBAT SIRUP YANG MENYEBABKAN GAGAL GINJAL DAN KEMATIAN) - Adelia Fairuz Wirawan, (2023)
This research is motivated by the existence of cases of acute kidney failure and death caused by consumption of drugs in the form of syrup and liquid containing dangerous substances. The purpose of this research is to analyze consumer protection regarding drug distribution and BPOM's role in this case. In researching the legal issues to be studied, the author will use the Normative Juridical method. In this study, the data analysis technique used by the author is a qualitative data analysis technique or also called continuous analysis, and is reinforced by field research in the form of direct interviews with the Republic of Indonesia's Food and Drug Supervisory Agency (BPOM). The case that will be discussed is about the GGAPA (Acute Renal Failure In Children) situation caused by the use of medicinal syrup. On October 10 2022, the Ministry of Health (Kemenkes) conducted an in-depth study regarding a suspected case of acute kidney dysfunction. Because there is a possibility that the syrup contains Ethylene Glycol (EG) and Diethylene Glycol (DEG) contaminants that exceed safe limits. The results of the study show that in terms of consumer protection, in this case the government violates consumer rights that they should have, one of which is the right to comfort, security and safety when consuming goods. Based on Presidential Regulation no. 80 of 2017 concerning the Drug and Food Control Agency Article 3 Paragraph (1) letter d, where BPOM should carry out supervision as long as drugs and food are distributed in a planned manner and carry out supervision as long as drug distribution is carried out before cases/problems occur, in this case BPOM does not This causes cases of acute kidney failure and death in children to emerge.